2021
DOI: 10.1115/1.4049844
|View full text |Cite
|
Sign up to set email alerts
|

Bioconvection of a Radiating Hybrid Nanofluid Past a Thin Needle in the Presence of Heterogeneous–Homogeneous Chemical Reaction

Abstract: : The photo catalytic nature of TiO_2 finds applications in medicinal field to kill cancer cells, bacteria and viruses under mild ultraviolet illumination and the antibacterial characteristic of Ag makes the composition Ag-TiO_2 applicable for various purposes. It can also be used in other engineering appliances and industries such as humidity sensor, coolants and in footwear industry. Hence, this study deals with the analysis of the effects of Magnetic field, thermal radiation and quartic autocatalysis of het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…The results obtained through this method are validated by comparing with the results of Suleman et al, 36 Puneeth et al, 19 and Shateyi and Motsa 27 . The comparison is found to be in good agreement with the existing literature and it is tabulated in Table 1.…”
Section: Solution Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…The results obtained through this method are validated by comparing with the results of Suleman et al, 36 Puneeth et al, 19 and Shateyi and Motsa 27 . The comparison is found to be in good agreement with the existing literature and it is tabulated in Table 1.…”
Section: Solution Methodssupporting
confidence: 75%
“…In view of these applications, several researchers have conducted studies on bioconvection 8–12 . The study of bioconvection due to the Stefan blowing over various surfaces, like, rotating disk, 13,14 bi‐axial stretching sheet, 15 solid rotating stretchable disk, 16 horizontal plate, 17 rotating cone, 18 thin needle, 19 and so forth, was extensively discussed by many mathematicians.…”
Section: Introductionmentioning
confidence: 99%
“…Nadeem et al [ 7 ] analyzed the heat transfer characteristics of hybrid nanofluid flowing over a curved surface. The nanomaterials various improved migrated phenomenon with subclass of base fluids was directed in communications Puneeth et al [ 8 , 9 ]. These continuations on the analysis of heat transfer of single-phase and double phase nanofluid were extended to ternary nanofluid by Manjunatha et al [ 10 ] which comprises of a base fluid and three different classes of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Suresh et al 24 experimentally studied the heat transfer of hybrid nanofluid and observed an enhancement in the friction coefficient and Nusselt number for the case of hybrid nanofluid. Puneeth et al 25 discussed the heat transfer of hybrid nanofluid past a thin needle in the presence of quartic autocatalysis. Labib et al 26 analyzed the effect of particle concentration and Reynolds number on the heat transfer performance in hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%